2018
DOI: 10.3758/s13428-017-0999-y
|View full text |Cite
|
Sign up to set email alerts
|

The failing measurement of attitudes: How semantic determinants of individual survey responses come to replace measures of attitude strength

Abstract: The traditional understanding of data from Likert scales is that the quantifications involved result from measures of attitude strength. Applying a recently proposed semantic theory of survey response, we claim that survey responses tap two different sources: a mixture of attitudes plus the semantic structure of the survey. Exploring the degree to which individual responses are influenced by semantics, we hypothesized that in many cases, information about attitude strength is actually filtered out as noise in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 77 publications
3
40
0
Order By: Relevance
“…Individual respondents may of course not always be as systematic or coherent in their responses, but the statistics of a sample will quite quickly converge around the semantically expected patterns, as happened in the present case. A recent study on STSR that separated attitude strength from semantic components in survey data found that correlation matrices are sometimes completely void of information about attitude strength, leaving only traces of semantics in the models (Arnulf, Larsen, & Martinsen, ; Arnulf, Larsen, Martinsen, et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Individual respondents may of course not always be as systematic or coherent in their responses, but the statistics of a sample will quite quickly converge around the semantically expected patterns, as happened in the present case. A recent study on STSR that separated attitude strength from semantic components in survey data found that correlation matrices are sometimes completely void of information about attitude strength, leaving only traces of semantics in the models (Arnulf, Larsen, & Martinsen, ; Arnulf, Larsen, Martinsen, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, it may be that semantic relationships are somehow different, twisted, or disregarded by certain subsamples. Personality, demographics, professional training, and interest in the subject matter are examples of factors that seem to affect the degree to which respondents comply with what is semantically given (Arnulf, Larsen, Martinsen, et al, ). LSA has already been used to identify schizophrenic from nonschizophrenic subjects in psychiatric diagnoses based on the patients' level of semantic predictability (Elvevag et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations